PENGARUH PENERAPAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK (PMR) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VII SMP MUHAMMADIYAH 1 PEKANBARU - Astuti, Rahmi Puspa Sari; Yuanita, Putri; Anggraini, Rini Dian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The background of this research is the low ability of students' problem solving of mathematics which causes the low result of the mathematics students learning. This research used experiment and use design non-equivalent control group design. Population in this research is ll of the first grade students in SMP Muhammadiyah 1 Pekanbaru. Sample of this research consists of two classes, there are class VII6 as the class experiment and VII5 as the class control. The purpose of this research is to know the effect of applying realistic mathematics eduacation approach to students' ability in mathematics problem solving in KD 3.4 Explain and state the sets, subsets, universe sets, empty sets, complement of sets and perfom binary operation on set using contextual problem and KD 4.4 Complete contextual problems related to the sets, subset, the universe sets, the empty sets, the complement of the sets, and the binary operations in the set. The research instrument used is the test of early mathematics ability obtained from the daily test in previous KD and test of mathematics problem solving (posttest). The result of the early mathematics ability test is used to determination the class sample. The result of the posttest were analyzed using the parametric statistical test of difference of two averages and the magnitude of influence calculated using Cohen's formula. The results of this reseach show that the applying realistics mathematics eduation approach give positive influence to students' ability in mathematics problem solving. The influence of realistics mathematics education approach has an impact of 76% on the problem solving ability of firat grade students of SMP Muhammadiyah 1 Pekanbaru and included in the medium category.Key Word : Realistics Mathematics Education, Ability in Math problem solving